CNTs-added PMNT/PDMS flexible piezoelectric nanocomposite for energy harvesting application - Promsawat, Napatporn; Promsawat, Methee; Janphuang, Phatthanapong; Beeby, Steve; Rojviriya, Catleya; Pakawanit, Phakkhananan; Pojprapai, Soodkhet (Taylor and Francis, 2018)
The flexible piezoelectric nanocomposites based on lead magnesium niobate titanate [Pb(Mg1/3Nb2/3)0.65Ti0.35O3; PMNT] particles in polydimethylsiloxane (PDMS) matrix were fabricated and characterized. PMNT powders are synthesized using the columbite precursor method. PMNT/PDMS flexible nanocomposites are then prepared by spin casting technique, where a small amount of carbon nanotubes (CNTs) is added into the PMNT/PDMS composite to enhance cross-links between PMNT particles and PDMS matrix. The phase and microstructure of the nanocomposite are investigated by using X-ray diffraction and scanning electron microscope (SEM). The electromechanical behavior is evaluated by using an autonomous pneumatic actuator. The flexible composite, occupying approximately 300 mm2, is capable of generating an open-circuit voltage (Voc) of 2.83 ± 0.24 V and a short-circuit current (Isc) signal of 0.33 ± 0.01 µA across 10 Ω resistor under mechanical load of 300 N. The generated electrical charges are 29026 pC. The relative dielectric constant is measured at 10 kHz and found to be 6.76 ± 1.15. The piezoelectric PMNT/PDMS composite can potentially be used in a variety of applications such as wearable sensors, actuators, and energy harvesting for converting kinetic energy into useful electrical energy.
Keywords: PMNT; polydimethysiloxane (PDMS); carbon nanotube; nanocomposite; energy harvesting